Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/aas.13600
|View full text |Cite
|
Sign up to set email alerts
|

Femoral nerve blocks for the treatment of acute pre‐hospital pain: A systematic review with meta‐analysis

Abstract: Background: Pain management is one of the most important interventions in the emergency medical services. The femoral nerve block (FNB) is, among other things, indicated for pre-and post-operative pain management for patients with femoral fractures but its role in the pre-hospital setting has not been determined. The aim of this review was to assess the effect and safety of the FNB in comparison to other forms of analgesia (or no treatment) for managing acute lower extremity pain in adult patients in the pre-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
(60 reference statements)
0
4
0
5
Order By: Relevance
“…It is part of a comprehensive literature review (PROSPERO registration number: CRD42018114399) of studies on pre-hospital analgesia, with the aim to provide the basis for a clinical guideline on the subject. The review has similar methodologies as described elsewhere [ 21 , 22 ]. The task force conducting the guideline was appointed by the Scandinavian Society of Anaesthesia and Intensive care medicine (SSAI) [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is part of a comprehensive literature review (PROSPERO registration number: CRD42018114399) of studies on pre-hospital analgesia, with the aim to provide the basis for a clinical guideline on the subject. The review has similar methodologies as described elsewhere [ 21 , 22 ]. The task force conducting the guideline was appointed by the Scandinavian Society of Anaesthesia and Intensive care medicine (SSAI) [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Three authors (LR and either KDF or PKH) independently assessed all titles and abstracts identified from the search according to the inclusion criteria, as described in our previous reviews [ 21 , 22 ]. References considered to be potentially relevant were collected and assessed independently in full text by two assessors using the same inclusion criteria [ 21 , 22 ]. Disagreements were resolved by discussion among all three assessors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dass es dennoch lohnt, dieses Thema wissenschaftlich adäquat zu beleuchten, zeigen erste Daten aus Deutschland zur RA bei dislozierten Extremitätenfrakturen, die positive Effekte nahelegen [33]. Umgekehrt zeigt eine erste Metaanalyse zur Analgesie bei proximalen Femurfrakturen den Bedarf an hochwertigen Studien mit adäquaten Vergleichsgruppen [34].…”
Section: Dank Gezielterunclassified
“…Lidocaine, bupivacaine, and ropivacaine have all been used within the out-of-hospital setting. 16,20 Local anesthetics have also been shown to still be effective at lower temperatures, with slight delays in onset times but no significant difference in duration of action. 21 While there are inconclusive data about the analgesic effect provided by warmed local anesthetics, there is limited information about the impact on the action time.…”
Section: Non-resource-heavymentioning
confidence: 99%